Paretic and Nonparetic Step Tests Are Noninterchangeable in Stroke: A Prospective Cohort Study. Issue 5 (12th February 2021) - Thilarajah, Shamala; Bower, Kelly J; Williams, Gavin; Clark, Ross A; Tan, Dawn; Pua, Yong-Hao
Abstract: Objective: The step test (ST) is a common clinical assessment of dynamic balance among survivors of stroke. The ST assesses a person's ability to place their paretic (paretic ST) or nonparetic (nonparetic ST) foot rapidly and repeatedly on and off a standardized block while standing. No study has formally explored if the 2 tests are interchangeable. Our study aimed to: (1) differentiate the correlates of paretic and nonparetic ST, and (2) compare their associations with physical function and falls. Methods: Eighty-one survivors of stroke were consecutively recruited from inpatient rehabilitation units (n = 4) and were assessed within 1 week prior to discharge. In addition to the ST, a handheld dynamometer and computerized posturography were used to measure lower limb muscle strength and standing balance, respectively. Self-selected gait speed and Timed Up and Go test were also assessed as measures of physical function. Falls data were monitored for 12 months post discharge using monthly calendars. Multivariable regression analyses were used to differentiate (1) the correlates of paretic and nonparetic STs, and (2) their associations with physical function and falls. Results: The median score for the paretic and nonparetic STs were 8 and 9 steps, respectively. Paretic ankle plantar-flexor and dorsiflexor strength were the strongest correlates of nonparetic ST, whereas both paretic ankle and knee extensor strength were the strongest correlates of paretic ST. In multivariable analyses adjusting for each other, both STs were independently associated with gait speed and Timed Up and Go scores. Paretic ST (odds ratio = 0.37; 95% CI = 0.22 to 0.62) was a stronger predictor than nonparetic ST (odds ratio = 0.51; 95% CI = 0.34 to 0.78) in predicting future falls. Conclusion: This study confirmed that the paretic and nonparetic STs are noninterchangeable. ST scores should be assessed separately to achieve a more complete interpretation. Impact: To our knowledge, this study is the first to objectively evaluate the similarities and differences between paretic and nonparetic STs. This information may refine the use and interpretation of the 2 STs for survivors of stroke.